Heidegger's silence - Lang, Berel (Cornell University Press, 1996)
"'This brilliant and compelling book deals with the relation between Heidegger's philosophy and his political-pedagogical career and, more generally, between the thought of a professional thinker and the everyday life of the person who has chosen the role of a philosopher.' Hayden White."--Bloomsbury Publishing.